Howard [surname unknown] correspondence - Howard, active 1863.
ALS (1863 March 20; Jackson, Tennessee) from Howard while serving in the Union Army to his cousin, Abbie, expressing his desire to rid the North of Southern sympathizers by hanging them.
Union Army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Treason -- United States; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Public opinion; Soldiers